Polymorphic Light Eruption: What's New in Pathogenesis and Management - Lembo, Serena; Raimondo, Annunziata (Frontiers in Medicine, 2018)
Polymorphic light eruption is the commonest photosensitive disorder, characterized by an intermittent eruption of non-scarring erythematous papules, vesicles or plaques that develop within hours of ultraviolet radiation exposure of patient skin. Together with the lesions, a terrible itch starts and increases with the spreading of the disease, sometimes aggravated by a sort of burning sensation. Clinical picture and symptoms can improve during the rest of the summer with further solar exposures.In the last years many advances have been performed in the knowledge of its pathogenesis andsome news have been proposed as preventive, as well as therapeutic options. All this has been discussed in the current mini review.